JURISDIÇÃO CONSTITUCIONAL, DEBATE PÚBLICO E EDUCAÇÃO INCLUSIVA: VOZ(ES) DA PARTICIPAÇÃO DEMOCRÁTICA NA AÇÃO DIRETA DE INCONSTITUCIONALIDADE Nº 6.590 - Pugliese, William Soares; Fracaro, Beatriz; Mello, Gislaine Cunha Vasconcelos (Revista da AJURIS, 2022)
CONSTITUTIONAL JURISDICTION, PUBLIC DEBATE, AND INCLUSIVE EDUCATION: VOICE(S) OF DEMOCRATIC PARTICIPATION IN THE DIRECT ACTION OF UNCONSTITUTIONALITY N. 6.590 ÁREA(S): direito constitucional. RESUMO: O artigo tem como objetivo analisar os diferentes argumentos suscitados no debate sobre o direito das pessoas com deficiência à educação inclusiva no âmbito da Ação Direta de Inconstitucionalidade nº 6.590, em trâmite no Supremo Tribunal Federal. Para tanto, emprega o método dedutivo e os procedimentos bibliográfico e jurisprudencial de pesquisa. A questão central em debate na ação é, em termos gerais, o significado da educação inclusiva, e se o locus ideal para seu desenvolvimento são escolas e classes regulares inclusivas, ou escolas e classes especializadas para alunos com deficiência. A interação entre a Corte e a sociedade civil se deu mediante emprego de dois instrumentos deliberativos institucionais no curso da ação: ingresso de amici curiae e realização de audiência pública. A diversidade argumentativa presente nas sustentações orais feitas por amici curiae, repisada e reforçada nas exposições em audiência pública, evidencia que a voz democrática, compreendida não enquanto voz da maioria, mas como voz da pluralidade social, nem sempre anseia percorrer o que, do ponto de vista do constitucionalismo, se mostra como caminho correto. Não obstante, essa aparente tensão será profícua se dela resultar uma decisão que leva em conta as razões canalizadas pela interação com a sociedade, mas acolhe apenas as alternativas interpretativas que estejam em conformidade com a ordem constitucional. É o que se espera da decisão definitiva. ABSTRACT: The article aims to analyze the different arguments raised in the debate about the right of people with disabilities to inclusive education in the scope of the Direct Unconstitutionality Lawsuit n. 6.590, currently pending in the Federal Supreme Court. To do so, it employs the deductive method and bibliographical and jurisprudential research procedures. The central issue under debate in the lawsuit is, in general terms, the meaning of inclusive education, and whether the ideal locus for its development is inclusive schools and regular classes, or specialized schools and classes for students with disabilities. The interaction between the Court and civil society took place using two institutional deliberative instruments during the case: the admission of amici curiae and a public hearing. The argumentative diversity present in the oral arguments made by amici curiae, repeated and reinforced in the presentations at the public hearing, shows that the democratic voice, understood not as the voice of the majority, but as the voice of social plurality, does not always aspire to follow what, from the standpoint of constitutionalism, is shown to be the correct path. Nevertheless, this apparent tension will be fruitful if it results in a decision that considers the reasons channeled by the interaction with society but welcomes only the interpretative alternatives that are in conformity with the constitutional order. This is what is expected from the final decision. PALAVRAS-CHAVE: direitos fundamentais; constitucionalismo e democracia; educação inclusiva; instrumentos deliberativos; pessoa com deficiência. KEYWORDS: fundamental rights; constitutionalism and democracy; inclusive education; deliberative instruments; person with disabilities. SUMÁRIO: Introdução; 1 Educação inclusiva como paradigma constitucional; 2 Decreto nº 10.502/2020 e a Ação Direta de Inconstitucionalidade nº 6.590; 3 A(s) voz(es) da sociedade sobre a educação para pessoas com deficiência: amici curiae e audiência pública na ADIn 6.590; Conclusão; Referências. SUMMARY: Introduction; 1. Inclusive education as a constitutional paradigm; 2. Decree No. 10.502/2020 and Direct Action of Unconstitutionality No. 6.590; 3. Society’s voice(s) on education for people with disabilities: amici curiae and public hearing at ADIn 6.590; Conclusion; References.